Corrosion Resistant Support Materials (CRSM) as Potential Development of Technical Parameters for Biocompatibility Testing of Bone Implant Products: A Review - Purwanto, Endi Hari; Lukiawan, Reza; Louhenapessy, Bendjamin Benny; Basuki, Budhy; Anggraeni, Putty; Darmayanti, Nur Tjahyo Eka (Jurnal Sains Materi Indonesia, 2024)
This study aims to describe the risk of bone implant material 316L-SS by identifying the material or materials or methods that are able to withstand the rate of corrosion or anti-corrosion. The method used is a literature study supported by tabulation data processing instruments, mind mapping, and fishbone diagrams. All journal literature is collected, grouped, carefully identified and scored to obtain information regarding its anti-corrosive material. The results show that corrosion of 316L can be coated with an anti-corrosive support material  as follows: 1) Alumina Sol-Gel, 2) Silane, 3) Parylene, 4) Niobium Oxide (Nb2O5), 5) 0.01%SS, 6) MgO/Tb,Eu-HAP, 7) Ti6Al4V coated HAP 40 micrometers, 8) HAP+HNO3, 9) Nano-HA, 10) Samarium- Gadolinium-HAP (Sm/Gd-HAP), 11) Nano-Thin Film Hydroxyapatite polylactic acid (nHA-PLA), 12) Multiwall Carbon Nanotube, 13) f-MWCNT, 14) Ag-HA/f-MWCNT nanocomposite, 15) nano HAP, 16) nano TiO2, 17) Double-HA, 18 ) Titanium ions, 19) Superhydrophilic TNT, 20) Superhydrophobic TNT, and 21) Ti-Nb-Zr-Ta6. Each element that coats 316L-SS has different characteristics of advantages, but unfortunately all existing literature does not explain the technical advantages of each type of CRSM. The advantages are explained by comparing the coating elements with one another.